2003
DOI: 10.2478/v10050-008-0073-3
|View full text |Cite
|
Sign up to set email alerts
|

Autumn migration of Marsh Harriers (Circus aeruginosus) across the Central Mediterranean in 2002

Abstract: Observations on the autumn migration of the Marsh Harrier were made at two sites of the central Mediterranean: the Circeo promontory (central Italy) and the island of Malta. The aim was to investigate the passage of birds belonging to different sex and age classes. At the Circeo promontory a total of 787 individuals was counted, 37.5% of which were juveniles. Over the island of Malta the passage of 1535 Marsh Harriers was recorded with an evident peak comprising 906 birds on 13 September. At both sites males o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 8 publications
(6 reference statements)
5
17
0
Order By: Relevance
“…Our results are consistent with previous surveys carried out during a single season in central (Circeo promontory; Agostini et al 2003) and southern Italy (Marcellinara Fig. 1) and confirm that adult birds are observed in larger numbers than juveniles, and that adult males are more frequent than adult females.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are consistent with previous surveys carried out during a single season in central (Circeo promontory; Agostini et al 2003) and southern Italy (Marcellinara Fig. 1) and confirm that adult birds are observed in larger numbers than juveniles, and that adult males are more frequent than adult females.…”
Section: Discussionsupporting
confidence: 93%
“…1) and confirm that adult birds are observed in larger numbers than juveniles, and that adult males are more frequent than adult females. This is in accordance with the hypothesis that adult males migrate over a longer distance to the wintering quarters in Africa, while many adult females (Agostini et al 2003) and many juveniles may stay in relatively higher latitudes during the winter (Agostini and Logozzo 2000;Panuccio et al 2005). In particular, age and sex composition of birds recorded in our study was similar to that recorded in previous surveys made in 1996 at the Marcellinara Isthmus (approx.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This fits with the results of visual observations carried out in the Mediterranean basin, both at migration bottlenecks and at wintering sites, that showed a stronger tendency for adult male Eurasian Marsh Harriers to migrate over longer distances than adult females, because an imbalance towards males has been observed during migration en route and from Africa, with the opposite trend at wintering sites in Italy (Agostini & Logozzo 2000, Agostini et al 2003, Panuccio et al 2005a, 2005b, 2012, Agostini & Panuccio 2010. It has been suggested that this latitudinal segregation of the sexes is promoted by sexual dimorphism, because females, being larger, are more adept than smaller males in taking larger prey items and coping with colder temperature, on the basis of the Bergman's rule (Cristol et al 1999, Panuccio et al 2005a.…”
Section: Discussionsupporting
confidence: 89%